CytoSorb Therapy in COVID-19 (CTC) Patients Requiring Extracorporeal Membrane Oxygenation: A Multicenter, Retrospective Registry - Song, Tae; Hayanga, Jeremiah; Durham, Lucian; Garrison, Lawrence; McCarthy, Paul; Barksdale, Andy; Smith, Deane; Bartlett, Robert; Jaros, Mark; Nelson, Peter; Molnar, Zsolt; Deliargyris, Efthymios; et al. (Frontiers in Medicine, 2021)
Introduction: CytoSorb extracorporeal blood purification therapy received FDA Emergency Use Authorization (EUA) to suppress hyperinflammation in critically ill COVID-19 patients. The multicenter CTC Registry was established to systematically collect patient-level data, outcomes, and utilization patterns of CytoSorb under the EUA. Methods: Patient-level data was entered retrospectively at participating centers. The primary outcome of the registry was ICU mortality. Patient disposition of death, continuing ICU care, or ICU discharge was analyzed up to Day 90 after start of CytoSorb therapy. Demographics, comorbidities, COVID-19 medications, inflammatory biomarkers, and details on CytoSorb use were compared between survivors and non-survivors in the veno-venous extracorporeal membrane oxygenation (ECMO) cohort. Results: Between April 2020 and April 2021, 52 patients received veno-venous ECMO plus CytoSorb therapy at 5 U.S. centers. ICU mortality was 17.3% (9/52) on day 30, 26.9% (14/52) on day 90, and 30.8% (16/52) at final follow-up of 153 days. Survivors had a trend toward lower baseline D-Dimer levels (2.3 ± 2.5 µg/mL vs. 19.8 ± 32.2 µg/mL, p=0.056) compared to non-survivors. A logistic regression analysis suggested a borderline association between baseline D-Dimer levels and mortality with a 32% increase in the risk of death per 1 µg/mL increase (p=0.055). CytoSorb was well tolerated without any device-related adverse events reported. Conclusions: CytoSorb therapy for critically ill COVID-19 patients on ECMO was associated with high survival rates suggesting potential therapeutic benefit. Elevated baseline D-Dimer levels may suggest increased risk of mortality. Prospective controlled studies are warranted to substantiate these results.